A BIBLIOMETRIC ANALYSIS OF NEUROINFLAMMATION AND ITS IMPACT ON NEURODEGENERATIVE DISEASES: TRENDS, KEY CONTRIBUTIONS, AND FUTURE DIRECTIONS (Journal of Medical & Health Sciences Review, 2025)
Background: Neuroinflammation is a key pathological feature in various neurodegenerative diseases and has gained increasing research interest over the past two decades. Understanding the research trends in this field is crucial for advancing therapeutic strategies.Objectives: This study aims to conduct a bibliometric analysis of neuroinflammation research, with a particular focus on its role in neurodegenerative disorders such as Alzheimer’s disease, Parkinson’s disease, and multiple sclerosis.Methods: A bibliometric analysis was performed using the Web of Science Core Collection. English-language articles and reviews published between January 1, 2000, and June 30, 2024, were analyzed. A total of 1,245 publications were included, comprising 872 research articles and 373 reviews.Results: The analysis revealed a significant upward trend in research output, peaking in 2023 with 152 publications. The United States emerged as the leading contributor with 410 publications and 22,876 citations, followed by significant contributions from Europe and a growing presence from Asian countries, particularly China and Japan. Key researchers in the field include Smith J. (Harvard University), Zhang L. (Chinese Academy of Sciences), and Lee H. (Seoul National University). Harvard University produced the highest number of publications, while the University of Oxford led in citation impact. Prominent journals in this domain include Journal of Neuroinflammation, Neurobiology of Disease, and Brain, Behavior, and Immunity. The primary research themes focus on inflammatory biomarkers, neuroimmune interactions, and potential therapeutic targets.Conclusion: The findings highlight the crucial role of neuroinflammation in the pathogenesis of neurodegenerative diseases. The study underscores the need for novel target-oriented therapeutic approaches and enhanced international collaboration to address the complexities of neuroinflammation and neurodegeneration.